Echocardiographic Profile of Hypertrophic Cardiomyopathy – A Single-Centre, Observational study - Islam, AKM Monwarul; Adhikary, Dipal K; Rahman, Shovan; Ahmed, Mohsin; Rahman, Md Toufiqur; Ullah, Mohammad; Majumder, Abdullah AS (Cardiovascular Journal, 2021)
Background: Hypertrophic cardiomyopathy (HCM) is an autosomal dominant disease of left ventricular hypertrophy (LVH). Phenotypic expression varies widely from subclinical hypertrophy to gross asymmetric septal hypertrophy causing left ventricular outflow tract (LVOT) obstruction. On top of genetic and phenotypic heterogeneity, the prevalence of different types of HCM may have geographical, as well as, ethnic variation. Methods: This observational study was carried out during 2010 to 2020 to determine the echocardiographic profile of HCM in Bangladeshi population. All patients undergoing transthoracic echocardiography (TTE) in a private consultation centre of Dhaka, Bangladesh were included. HCM was defined as the presence of a maximal end-diastolic wall thickness of e”15 mm anywhere in the left ventricle (LV), in the absence of another cause of hypertrophy in adults. HCM was further classified according to the pattern of myocardial hypertrophy and presence or absence of LVOT, or mid-left ventricular cavity obstruction. Results: Out of 76 cases, non-obstructive HCM was the commonest type (65.8%), followed by HCM causing LVOT obstruction (13.2%), HCM causing mid-LV cavity obstruction (10.5%), and the apical variety ( 10.5%). Asymmetric septal hypertrophy (ASH) was found in 42.1%, systolic anterior motion (SAM) of anterior mitral leaflet (AML) in 14.5%, mitral regurgitation (MR) in 50%, left ventricular systolic dysfunction in 5.3%, and raised pulmonary artery systolic pressure (PASP) in 15.8% of cases. Maximum LV wall thickness ≥30 mm was found in 66 out of 76 cases. Conclusion: The study highlights the clinically useful profile of HCM in Bangladeshi population based on conventional echocardiography. Further studies involving clinical, newer echocardiographic modalities and genetic analyses are warranted to discover the additional information in this ethnicity. Cardiovasc j 2021; 14(1): 5-11